Currículo como rasura, performance como pele - Melotti, Ana Carolina Justiniano (2021)
This research draws on the notion of performance in the field of education as the invention of a curriculum whose creations give rise to a new skin and its effects are insurrections that undo official versions. It explores creations and movements that erase the curriculum of a public school through performance as a skin. It claims the skin beyond physical the physical one, as an invented skin and as a place of unfolding. Performance is, thus, conceived as what is produced in the strata of skinpassage to intensive states of anonymous forces, existences, as well as a power to be affected. It defends performance as an invention made when its movements challenge the representation imposed to education through strangling policies. It emphasizes the political strength of public schools in the creation of performances that are invented in diverse everyday contexts, and empowers creation as a way to collectively resist. It problematizes the need to highlight insurgences and creative movements in times of toxic policies through the cartography of movements in a public high school in Serra, located in Vitória (ES- Brazil). It evokes the need to create getaways in order to face continuous attacks that have been waged against life. It highlights inventive processes as weapons to disrupt the conservative machine's anti-production process against the game of homogenizations. It grounds on the concepts of Deleuze and Guattari to think of the game of difference as an escape and concludes that performance is an invention that ventilates and produces effects in contact with the forces of the world by creating other possible skins and other temporalities.